2009
DOI: 10.1080/00304940903102739
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of Wogonin, A Flavonoid Natural Product with Extensive Pharmacological Activity

Abstract: Wogonin (5,7-dihydroxy-8-methoxyflavone, 5), a flavonoid natural product first isolated from Scutellaria Radix, is well-known for its anti-inflammation, 1 anti-allergy, 2 anti-tumor 3 and anti-hepatitis B virus 4 properties. Owing to its extensive applications in medical treatment, researchers have developed several synthetic pathways to obtain this important natural product since the early part of the last century. 5, 6 The initial total syntheses of wogonin were based on the common synthetic approaches to fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Wogonin (purity ≥99%) was synthesized and used in all experiments unless otherwise indicated[45]. The final concentration of dimethyl sulfoxide (DMSO) in all experiments was ≤0.01%, and cells treated with the highest concentration of DMSO were used as controls in the corresponding experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Wogonin (purity ≥99%) was synthesized and used in all experiments unless otherwise indicated[45]. The final concentration of dimethyl sulfoxide (DMSO) in all experiments was ≤0.01%, and cells treated with the highest concentration of DMSO were used as controls in the corresponding experiments.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicated that compound 5 might induce higher level of caspase-dependent apoptosis than cisplatin in cisplatinresistant cancer cells. The CFA assay (CFA) is an extensively used and wellestablished method for testing chemotherapeutic agents in vitro (Li et al, 2009), reflecting the ability of chemotherapeutic agents to prevent the cell from dividing. To further detect the effect of cell proliferation inhibition of compound 5, we used the colony forming assay to compare the ability of compound 5 and cisplatin to prevent the proliferation of cisplatin-sensitive A549 and cisplatin-resistant A549/CDDP cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Three synthetic approaches toward 1 have been reported . Rao’s route in 1947 selected chrysin ( 2 ) as a starting material to obtain 1 through O7-benzylation, oxidation, methylation, and debenzylation (Scheme , Route A) .…”
Section: Resultsmentioning
confidence: 99%